APPLICATION OF PIT HEAT METHOD IN SANGGAI MACHINE TECHNOLOGY AS A ORGANIC PRESERVATIVE OF FOOD - Dede Martino; Ardiyaningsih Puji Lestari; Linda Handayani (Prodi Fisika FST UNJA, 2019)
Indonesia is a country that has extraordinary natural resources, both biological and non-biological natural resources. Indonesia has a great opportunity in utilizing natural resources to improve the welfare of the people. Unfortunately, Indonesia has not been yet able to exploit all of that. The prices of agricultural products are quite high but ironically the welfare of farmers has not improved either. On the other hand, other natural resources from the marine and earth sector also have export potential, but in fact these potentials have not had a significant influence. One of the causes of the suboptimal use of natural resources in Indonesia is the lack of integration of technology in developing the potential of the biodiversity. One of the efforts made to optimize the potential for life is to apply the concept of physics, which uses the concept of pit heat in the “sanggai” engine technology. This machine can be used to optimize the potential of agriculture in Indonesia. Pit heat technology can dry food without damaging the vitamin content. This technology does not damage the protein structure of food substances so that the application of technology on this machine can be used to optimize the potential of agriculture in Indonesia.